Analysis of the Thermal Elastohydrodynamic Lubrication Property of Water Lubrication Tenmat Bearing with Considering the Liquid Inertial Force - Dong Ning; Zhang Yongbin; Wang Youqiang; Liu Qian; Huang Xingbao (Jixie chuandong)
Considering the inertial force in Reynolds equation,the thermal elastohydrodynamic lubrication analysis of the water- lubricated tenmat journal bearing is varied out. The effects of load,speed and surface roughness on the pressure and film thickness are discussed,and then compared with those without considering inertial force. The result show that as the fluid inertial force is considered,the pressure in inlet region,the central film thickness and the minimum film thickness are increased,but the pressure peak is decreased. The pressure peak is increased with the increase of load,but the film thickness is decreased. The pressure peak is decreased with the increase of speed,but the film thickness is increased. Considering the bearing surface roughness make pressure and film thickness oscillating,the pressure peak increased,the minimum film thickness decreased.